Adaptive Epitaxy of C-Si-Ge-Sn Customizable Bulk and Quantum Structures - Concepción, Omar (Advanced materials (Deerfield Beach, Fla.), 2025)
© 2025 The Author(s). Advanced Materials published by Wiley‐VCH GmbH.